A case report of jejunum transplantation in the treatment of severe cervical esophageal stricture in patients with dystrophic epidermolysis bullosa - Xu, Zhen; Zhang, Yong; Hu, Yanjiao; Xiu, Xia; Yang, Bowen; Huang, Tianqiao; Huang, Yichuan (Frontiers in Oncology, 2023)
Epidermolysis bullosa (EB) is a rare disorder caused by autosomal genetic variation. Its main clinical features include skin and mucous membrane blisters, erosion, repeated ulcers and scar formation. The lesions mostly involve the skin, oral cavity, digestive system and urinary system. Epidermolysis bullosa complicated with esophageal stenosis is a common gastrointestinal manifestation of this disorder. Currently, there is no cure for EB, and thus symptomatic treatment is usually applied. Here we describe the case of a patient with recessive dystrophic EB complicated with severe esophageal stenosis. The narrow segment of esophagus was removed and the free part of jejunum was transplanted into the esophageal defect to reconstruct the esophagus and restore the patient's normal swallowing. For patients with EB complicated with severe esophageal stenosis, surgical resection of the diseased esophagus and jejunal transplantation can be used to repair the esophageal and restore normal swallowing pathway, providing an effective treatment for this condition.